(untitled) (Bangladesh Journal of Public Administration, 2024)
Containing inflation has been a major challenge in the macro-economic governance of Bangladesh in recent years particularly after the outbreak of Covid-19 pandemic and Russia-Ukraine war. However, recent monetary statements are imposing a gradual tightening of the money supply by increasing policy rates and restraining Government expenditure. Henceforth, which orientation of macroeconomic governance is perceived as more comfortable to people in coping up with the post-2020 inflation requires deliberate analysis. This paper explored this knowledge gap with a special focus on two trends of `inflation tackling measures: price stability and income growth’ from a public policy perspective. Key Informant Interview (KII) methods were used to carry out this study. Then thematic analysis was done on some specific issues like, local factors of inflation, linkage of local factors with price inflation, the effectivity of price stability and income growth orientation, Finally, it was inferred that, price stability is a priority over income growth in tackling inflation. Focus on price stability promotes the synergic outcome of other monetary and non-monetary efforts, which, in the long run, promotes income growth consequently. However, a number of local factors, predominantly insufficient efficiency in the managing market appeared as a determinant of home-grown factor of price inflation in Bangladesh; so, the paper suggests that proper flow and movement of supply chain requires exigent attention to deal with post-2020 inflation.